Analisis Laporan Keuangan Berdasarkan Rasio Keuangan PT. Gudang Garam Tbk (International Forum of Researchers and Lecturers, 2024)
The purpose of this analysis is to find out how the company’s financial performance is based on financial ratios. This is important to measure and evaluate, so that you can get a comprehensive picture of your financial position. This research method uses quantitative descriptive methods with data documentation. The financial report analysis method involves several financial ratios, namely liquidity, solvency and profitability ratios. The results of the discussion showed that the financial performance of PT. Gudang Garam Tbk shows fluctuating ratios every year, this is due to increases or decreases in financial report items, for example sales, inventory, profits and others.